Membrane Attack Complex C5b-9 Promotes Renal Tubular Epithelial Cell Pyroptosis in Trichloroethylene-Sensitized Mice - Wang, Feng; Huang, Meng; Wang, Yican; Hong, Yiting; Zang, Dandan; Yang, Chunjun; Wu, Changhao; Zhu, Qixing (Frontiers in Pharmacology, 2022)
Trichloroethylene (TCE), a commonly used organic solvent, is known to cause trichloroethylene hypersensitivity syndrome (THS), also called occupational medicamentosa-like dermatitis due to TCE (OMDT) in China. OMDT patients presented with severe inflammatory kidney damage, and we have previously shown that the renal damage is related to the terminal complement complex C5b-9. Here, we sought to determine whether C5b-9 participated in TCE-induced immune kidney injury by promoting pyroptosis, a new form of programed cell death linked to inflammatory response, with underlying molecular mechanisms involving the NLRP3 inflammasome. A BALB/c mouse-based model of OMDT was established by dermal TCE sensitization in the presence or absence of C5b-9 inhibitor (sCD59-Cys, 25μg/mouse) and NLRP3 antagonist (MCC950, 10mg/kg). Kidney histopathology, renal function, expression of inflammatory mediators and the pyroptosis executive protein gasdermin D (GSDMD), and the activation of pyroptosis canonical NLRP3/Caspase-1 pathway were examined in the mouse model. Renal tubular damage was observed in TCE-sensitized mice. GSDMD was mainly expressed on renal tubular epithelial cells (RTECs). Caspase-1 dependent canonical pathway of pyroptosis was activated in TCE-induced renal damage. Pharmacological inhibition of C5b-9 could restrain the caspase-1 dependent canonical pathway and rescued the renal tubular damage. Taken together, our results demonstrated that complement C5b-9 plays a central role in TCE-induced immune kidney damage, and the underlying mechanisms involves NLRP3-mediated pyroptosis.